RESEARCH ON THE PHYTOREMEDIATION OF SOIL CONTAMINATED WITH HEAVY METALS FROM MINING ACTIVITY: CASE STUDY BALOMIR-URICANI TAILINGS DUMP - MĂDĂLINA F. IONIȚĂ; SORIN M. RADU; EMILIA C. DUNCA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This study evaluates the ability of various plant species to adapt and grow in heavy metal-contaminated soils, using the Balomir-Uricani tailings dump as a case study. Soil samples were collected from 17 points and analyzed for heavy metal content using atomic absorption spectrometry. In the lab, two phytoremediation methods-phytostabilization and phytoextraction-were tested using three types of plants: hyperaccumulators, phytostabilizers, and phytoextractors. The results highlight the importance of selecting the suitable species for phytoremediation, as those thriving at the Balomir-Uricani site show promise for rehabilitating soils contaminated by mining activities.